2004
DOI: 10.1016/j.jcat.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of the water–gas-shift activity of Pd/ceria by Mo

Abstract: The effect of surface Mo on the water-gas-shift (WGS) activity of Pd/ceria was studied. A series of 1-wt% Pd catalysts, with varying Mo content, were prepared from supports obtained by aqueous impregnation of (NH 4 ) 2 MoO 4 onto ceria. Rates were found to decrease linearly with Mo coverage up to 1.8 Mo/nm 2 and were 10% of that on Pd/ceria after the addition of this amount of Mo. TPD studies with 2-propanol on the Mo-containing ceria demonstrate a relationship between the loss of WGS activity and ceria sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…However, the more than 90% decrease the intensities of these two bands after exposure to flowing O 2 for 12 h at room temperature (figure 3) provides a strong driving force to consider alternative assignments to carbonate for the 1582-1600 and 1331-1340 cm )1 bands observed in this investigation, even though their formation under conditions similar to those used in the present work has been reported [3,41]. Carbonates of ceria are notoriously stable [10], and no apparent change in the spectra of CO adsorbed on CeO 2 occurs after dosing O 2 on CeO 2 preadsorbed with CO according to Li et al [26].…”
Section: Discussionmentioning
confidence: 57%
“…However, the more than 90% decrease the intensities of these two bands after exposure to flowing O 2 for 12 h at room temperature (figure 3) provides a strong driving force to consider alternative assignments to carbonate for the 1582-1600 and 1331-1340 cm )1 bands observed in this investigation, even though their formation under conditions similar to those used in the present work has been reported [3,41]. Carbonates of ceria are notoriously stable [10], and no apparent change in the spectra of CO adsorbed on CeO 2 occurs after dosing O 2 on CeO 2 preadsorbed with CO according to Li et al [26].…”
Section: Discussionmentioning
confidence: 57%
“…3 [5,13,15,[37][38][39][40][41]. The one route is dehydrogenation of ethanol to produce CH 3 CHO, then CH 3 CHO is decomposed and then the steam reforming of CH 4 , and so on.…”
Section: Variations Of Ethanol Conversion and Product Distribution Wimentioning
confidence: 99%
“…Sketch map of reaction pathway for catalytic steam reforming of ethanol[5,13,15,[37][38][39][40][41].…”
mentioning
confidence: 99%
“…The effect of Mo addition to Pd/Ceria catalysts was studied by Zhao et al [17]. The authors found a reduction in WGS activity with increasing Mo loading.…”
Section: Introductionmentioning
confidence: 99%